Fifteenth General Review of Quotas-Quota Formula and Realigning Shares. (Policy Papers; Policy Paper ;, 2021)
This paper provides background for an initial discussion under the Fifteenth General Review of Quotas (15th Review) in line with the work plan agreed by the Executive Board. It discusses issues related to further reforms of the quota formula and realigning quota shares, based on updated quota data through 2015. A companion paper, to be discussed separately, will address issues related to the size of the Fund and mix of quota and borrowed resources. Both these papers seek to facilitate initial discussions on some of the key issues for the 15th Review. No proposals are made at this stage, recognizing that further deliberations will be needed before the issues under discussion can begin to be narrowed down.